Statistical analysis of colour changes in tempera paints mock-ups exposed to urban and marine environment. (March 2018) - Rivas, T.; Pozo-Antonio, J.S.; Barral, D.; Martínez, J.; Cardell, C.
Highlights: Vectorial and functional statistical analysis evaluate colour evolution of tempera paint mock-ups under outdoor exposure. Functional approach provided more useful information than the vectorial one. Different colour evolution found on gypsum, haematite, lapis lazuli and azurite paint temperas. Nature and stability of binder under outdoor exposure is key to understanding atypical colour changes. Abstract: The aim of this study is the exploration of the suitability of two different statistical approaches (vectorial and functional analyses), which go beyond a purely descriptive statistics, in order to identify trends and similarities in colour changes of several tempera mock-ups paints during thirteen months. The samples were subjected under an outdoor exposure to a natural urban atmosphere characterized by an important marine and industrial influence. The changes of the colour were measured in CIE L ∗ a ∗ b ∗ and CIE L ∗ C ∗ h colour spaces The paint mock-ups were binary mixtures made with either egg yolk or rabbit glue binder, mixed with one of the seven pigments studied, some of which have different grain sizes. Two different statistical analyses – vectorial and functional – were performed in order to detect the different colour change evolution among the temperas during the exposure time. The functional approach revealed more useful information than the vectorial (classic) one. Paints containing haematite, lapis lazuli and (standard grain size) azurite exhibited different trends of the colour parameters in comparison with the rest of the paints. Stereomicroscopy, X-ray diffraction and Fourier transform infrared spectroscopy showed that the binder composition and especially its stability to outdoor exposure, are the factors responsible for the statistically significant colour changes detected.